2006
DOI: 10.1007/s10182-006-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

The operating characteristic of double sampling plans by variables when the standard deviation is unknown

Abstract: Double sampling plan by variables, double-stage t-test, JEL C00, C12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Numerical examples will be presented in the doctoral dissertation of A. Rohr. Krumbholz and Rohr (2006) showed that the one-sided two-stage t-test may be interpreted as a special double plan by variables in Case (ii). The OC procedure of Krumbholz/Rohr can also be used to calculate the OC of the two-sided two-stage t-test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerical examples will be presented in the doctoral dissertation of A. Rohr. Krumbholz and Rohr (2006) showed that the one-sided two-stage t-test may be interpreted as a special double plan by variables in Case (ii). The OC procedure of Krumbholz/Rohr can also be used to calculate the OC of the two-sided two-stage t-test.…”
Section: Discussionmentioning
confidence: 99%
“…But their formula seems to be not constructive enough in that sense that it could serve as basis for an algorithm. Krumbholz and Rohr (2006) proved a formula expressing P (A 2 ) as a triple integral which could be implemented in an algorithm. This algorithm led to the first available procedure, as far as we know, allowing to calculate the OC L δ (p) exactly for an arbitrary p. Throughout the present paper, this procedure will be employed.…”
Section: Notation and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sommers (1981)) to calculate L(θ ) using normal approximations. Krumbholz and Rohr (2006) succeeded in programming an algorithm to calculate exactly the OCL of the double sampling plan for variables with unknown variance and a one-sided tolerance limit. This tolerance limit U may be assumed to be an upper one without any restriction.…”
Section: Remarkmentioning
confidence: 99%